KEPUASAN KARYAWAN TERHADAP KOMPENSASI DAN PENILAIAN KINERJA (Studi Kasus di Perusahaan X) - Regina Detty (Center for Economic Studies Universitas Katolik Parahyangan, 2013)
Banking institutions is one of the businesses that have a competitive climate, where change and innovation banking services happen very quickly, it requires the company to keep pace with the changes and survive the competition that kept rolling, and therefore very important for the company to optimize its resources, the main one of which is human resources. SDM is a live production factors, where each company has their own way of doing the development of human resource management, human resources management but is commonly applied in the company. In the face of any change, HRM should be able to match what is needed to deal with these changes and achieve company goals. for that, we need the collective contribution of human resources, so that the necessary performance management activities, because if the human resources in the company can understand the contribution expected from them and have received support, the understanding of the purpose and job satisfaction will increase (Costello, 1994:6) so that the ideal of understanding and its application will affect the job satisfaction of human resources. This study aimed to determine the effect of the implementation of the performance management and compensation on employee job satisfaction in Bank X where this study took a sample of some branches that are supposed to represent and employees were asked to complete a questionnaire and interviews. Results of questionnaires collected was processed and the analysis of qualitative and quantitative. From these results it can be concluded that the salary provided by Bank X sudan pretty good but still needs to be improved periodic salary increases in accordance with the increase in cost of living and Bank X still need to also increase the benefits and facilities provided to the employees. Moderate Performance Management at Bank X still have to reduce the level of subjectivity superiors and also need to clarify the standard in accordance with IEC standards work in each job position.